P-161 The necessity of data to support service development. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Black, Rachel; Dempster, Tracie; Ward, Beth
Abstract : Novel data sources and analyses of statutory data are highlighting challenges and opportunities for the children's palliative care sector. Such services have a growing evidence base for their work which includes some of the most robust demographic data to date (Fraser et al . 2011, 2013). Articulating how to channel the knowledge gained into effective service developments is a key challenge for children's hospices. One example of using data to challenge existing thinking and evolve evidence based services concerns post death care. Child Death Overview Processes [CDOP] facilitate annual reporting of child mortality. Of the child deaths reviewed in 2014, over 80% had ongoing health problems and 70% had a known life-limiting or life-threatening condition (DfE 2014). Children's hospices provide end of life care. Post death care may also be offered, providing an alternative to mortuary or funeral home for the child's body and facilitating immediate bereavement support forextended family. Not all children's hospices provide this service. Of those that do, practice varies with respect to service provision for families whose child has not accessed the hospice in life and who may not fulfil hospice access criteria. Not extending the service to such families may reflect anxiety among children's hospices that their bereavement services will be overwhelmed by numbers of families requiring the service. This paper seeks to address those concerns and contextualise appropriate service development utilising local and national data sources. Local CDOP data are reviewed for a number of children's hospices and compared to bed availability for end of life care and post death care services, alongside a review of the evidence of the impact of provision or not of provision of such services upon family grieving and morbidity.